Control of Time Scale Dynamical Systems with an Application to Concurrency Control for Real-time Database Systems - Ramesh Babu, N.; Murty, K.N.; Balaram, V.V.S.S.S. (Інститут проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
Main objective in this paper is to unify results on controllability and observability on time scales and deduce the results of classical theory as a particular case and then resolve the time constraints on concurrency control by incorporating jump operators on time scale dynamical systems. Обобщены результаты исследований управляемости и наблюдаемости при масштабировании во времени. Получены результаты классической теории как частного случая, при этом устранены ограничения по времени при параллельном управлении операторами перехода для динамических масштабируемых систем. Узагальнено результати досліджень керованості та спостережуваності при масштабуванні за часом. Отримано результати класичної теорії як окремого випадку, при цьому усунуто обмеження за часом при паралельному керуванні операторами переходу для динамічних систем, що масштабуються.